PERAN SUPERVISI AKADEMIK DALAM PENINGKATAN KOMPETENSI PEDAGOGIK GURU DI MARKAZ AL-ZAMIL AL-MA’TUQ - Nisa Putri Wulandari; Siti Qomariyah; Vera Siti Magfiroh; Salma Tsana Fi Sa’adah; Venti Fatmawati Suhendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Based on the research findings, academic supervision at Markaz Al Zamil Al Ma’tuq is implemented systematically and continuously through teacher administrative supervision and classroom instructional supervision. Academic supervision functions not only as an evaluative activity but also as a form of professional development that contributes to the improvement of teachers’ pedagogical competence. Administrative supervision ensures the readiness of instructional planning, while classroom supervision directly supports the improvement of pedagogical practices. The implementation of supervision that is adjusted to the characteristics of different subjects reflects a contextual approach aligned with the academic culture of the Islamic boarding school. The tiered follow-up actions—ranging from professional coaching and repeated supervision to temporary teaching suspension—demonstrate the institution’s commitment to maintaining instructional quality and reinforcing teachers’ professional responsibility. Thus, academic supervision plays a strategic role in improving the quality of learning in the pesantren context. Strengthening a sustainable supervision system and fostering teachers’ openness to supervisory feedback are essential for the continuous development of pedagogical competence. Future studies are recommended to examine academic supervision using more diverse methodological approaches in order to obtain a more comprehensive understanding of its impact on the quality of education in Islamic boarding schools.